Livelihood Missions and Economic Improvement in Nagaland: An Empirical Study - Singh, Gurdev (Journal of Global Economy, Business and Finance, 2026)
With the aim of strengthening the economy, authorities in Nagaland have launched a series of livelihood missions. These initiatives aim to help the people of Nagaland improve their standard of living by providing them with better access to employment and higher levels of income. Livelihood missions have made important contributions to the state's economic growth through a number of different projects and programs. In Nagaland, agriculture and related industries greatly benefit from livelihood missions. Since the state's economy is largely dependent on agriculture, these initiatives aim to modernize farming methods, expand access to those methods, and increase the value of agricultural outputs. Livelihood missions boost farmers' incomes and the economy as a whole by improving agricultural productivity and efficiency. Micro, small, and medium-sized enterprise (MSMEs) development is a primary focus of livelihood initiatives in Nagaland. These envoys aid micro, small, and medium-sized enterprises (MSMEs) monetarily, technically, and in terms of marketing and infrastructure. Supporting the expansion of micro, small, and medium-sized enterprises (MSMEs) is one way that livelihood missions help advance economic growth for everybody.The methodology undertaken is descriptive analysis. The objectives are first to discuss the role and importance of livelihood missions, second one is to knowthe importance of Micro-Enterprises, and third is significance of rural development.